O conceito de variável: o Modelo 3UV nos exercícios de uma coleção de livros didáticos para os anos finais do Ensino Fundamental - Paula, Jamirley Priscila de Souza de (2019)
This dissertation had as its objective to investigate how the concept of variable is being approached according to the 3UV Model (three uses of the variable), in the exercises of a collection of textbooks used in the final years of Basic Education. To fundament or investigation, we used the 3UV Model developed by Sonia Ursini, Maria Trigueros and collaborators, through which is postulated that to have adequate comprehension of the variable concept it is necessary to know the different uses of the variable with its respective characteristic aspects. The 3UV Model contemplates three main uses of the variable in Basic Education: unknown, generic number and functional relation. The adopted methodology was Content Analysis of Laurenice Bardin. Though we highlight that only a few elements of the suppositions were mobilized to analyze the four volumes of the chosen Collection: Coleção Projeto Teláris Matemática (Mathematic Teláris Project Collection) of the author Luiz Roberto Dante. As a supposition, we adopted the importance of having a directed critical view on the textbooks in general. We developed criterias based on the 3UV Model to qualitatively analyze the four volumes that form this Collection. Through the analyses held in the four volumes of the Collection, we counted 344 exercises referring to the use of a variable as an unknown, 20 to the use as a generic number and 57 referring to the use as a functional relation. Regarding the integrating activities (those which simultaneously mobilize at least two different uses of the variable) two were counted in the volume of the 6th grade, 4 in the volume of the 7th and 5 in the 9th, in total 11 activities were considered integrating in the Collection. We noted that unknown was the most privileged use of the variable in relation to the rest, and in this sense, we emphasize that privileging only one determined use of the variable can limit the knowledge of the students on the concept